Exploring Emotions at Organization Level: Emotional Intelligence Framework (EQF) an Integrative Approach Towards Universal Definition of EQ. - Faryal Razzaq,; Sana Ashfaq,; Muhammad bin Ashfaq, (IBT- JOURNAL OF BUSINESS STUDIES, 2022)
Emotional Intelligence (EQ) is considered to be an important attribute to succeed at top level of management and is a distinguishing factor among top performing employees at workplace. However, the variance in literature points towards the gap of the discrepancy in the elements of EQ models entailing to work towards a holistic, multilevel and sequential model. To address afore said discrepancies, a humble effort is made to present a revised comprehensive framework of EQ. A detailed theoretical analysis for EQ dimensions helped to identify the domain of new Contents for the existing construct of EQ which were regrouped into three constructs of Emotional Appreciation (EA), Emotional Application (EL) and Emotional Maturity (EM). The proposed Model disambiguate EQ as exhaustibly as possible in a hierarchical and sequential manner to allow reasoning about their property working towards an integrated framework of all the elements of influential EQ models as suggested by practitioners. The proposed model will be a valuable tool for managers and academia as it incorporates all the dimensions of EQ and present a logical hierarchical model and is a modest attempt to work towards a universal definition of EQ.